Kajian program kesehatan jiwa masyarakat di puskesmas Kabupaten Minahasa - Dali, Farrand Ivan; Ottay, Ronald I.; Palandeng, Henry M. F. (UNIVERSITAS SAM RATULANGI, 2019)
Mental health is defined as a state of well-being where an individual realizes his own potential, can cope with the stress of life, work productively, and is able to actively contribute to society. Minahasa Regency ranks 8th out of 15 districts in the Province of North Sulawesi on the reported number of cases of mental health issues. This study aims to provide an overview of the mental health programs in primary healthcare centers in Minahasa Regency. The research design used is a cross-sectional descriptive approach. This study is conducted on three primary healthcare facilities operating in the area of Minahasa Regency during November 2019. The study shows that the mental health program running in Minahasa Regency is still not optimal. Mental Health Service Programs in primary healthcare facilities in Minahasa Regency is still not optimal due to the lack of training and fundingKeywords: Mental Healthcare Programs, Minahasa